Hard real-time communication for mobile ad hoc networks - Hughes, Barbara (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2007)
The increasing availability of wireless local area networking, particularly ad hoc networking, has lead to the evolution of new application domains, such as inter-vehicle communication and communication between autonomous mobile robots. Real-time communication is essential to allow applications in these domains to be realised. The characteristics of a mobile ad hoc network, typified by host mobility, unpredictable resource availability and time-varying connectivity, pose challenges for providing hard real-time communication guarantees in this domain. An approach adopted by previous real-time communication models is to adapt the communication time bounds to reflect the dynamics of the network. However, allowing time-bound adaptation implies that only soft real-time communication is available and, critically, that hard real-time communication is not. This thesis describes a new communication model, the space-elastic model, to provide hard realtime communication for applications with guaranteed response-time requirements in wireless networks in general, and ad hoc networks in particular. In addition, a new real-time ad hoc routing protocol, the Space-Elastic Adaptive Routing (SEAR) protocol, is described, which provides the basis of a real-world implementation of the space-elastic model. The contributions of this thesis are two-fold. Firstly, the space-elastic model is proposed to enable hard real-time communication by using specified geographical bounds to scope the area within which timely communication must be guaranteed in a wireless network. Due to network dynamics the space or actual coverage within which timely communication is guaranteed may be adapted over time with timely adaption notification to higher layers when a space adaptation occurs. No change is made to the specified communication time-bounds within the actual coverage. Secondly, a new location-aware real-time ad hoc routing protocol, SEAR, coupling time-bounded route discovery and maintenance with dynamic resource reservation has been designed and implemented. An evaluation of the spaceelastic model, using SEAR, shows that time-bounded communication is possible within the actual coverage and that time-bounded notification can be provided if adaptation occurs.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin